A self-healing polymerized-ionic-liquid-based polymer electrolyte enables a long lifespan and dendrite-free solid-state Li metal batteries at room temperature. Issue 3 (5th January 2023) - Lin, Xiujing; Xu, Shiyuan; Tong, Yuqi; Liu, Xinshuang; Liu, Zeyu; Li, Pan; Liu, Ruiqing; Feng, Xiaomiao; Shi, Li; Ma, Yanwen
Abstract : We introduce a self-healing polymerized-ionic-liquid-based polymer electrolyte for solid-state Li metal batteries, which can spontaneously reconstruct dendrite-induced defects at the Li/electrolyte interface, and, in turn, tailor Li deposition. Abstract : The implementation of high-safety Li metal batteries (LMBs) needs more stable and safer electrolytes. The solid-state electrolytes (SSEs) with their advantageous properties stand out for this purpose. However, low Li/electrolyte interfacial instability and uncontrolled Li dendrites growth trigger unceasing breakage of the solid electrolyte interphase (SEI), leading to fast capacity degradation. In response to these shortcomings, a new type of polymer electrolyte with self-healing capacity is introduced by grafting ionic liquid chain units into the backbones of polymers, which inherits the chemical inertness against the Li anode, allowing high Li + transport, wide electrochemical window, and self-healing traits. Benefiting from the strong external H-bonding interactions, the obtained polymer electrolyte can spontaneously reconstruct dendrite-induced defects and fatigue crack growth at the Li/electrolyte interface, and, in turn, help tailor Li deposition. Owing to the resilient Li/electrolyte interface and dendrite-free Li plating, the equipped Li|LFP batteries display a high initial specific capacity of 134.7 mA h g −1, rendering a capacity retention of 91.2% after 206 cycles at room temperature. The new polymer electrolyte will undoubtedly bring inspiration for developing practical LMBs with highly improved safety and interfacial stability.